The Influence of Capital Structure, Profitability, Good Corporate Governance on Earnings Quality and Its Impact on Company Value - Nisrina Septiarini; Hari Setiyawati (Green Publisher Indonesia, 2024)
The primary aim of this research is to examine the impact of Capital Structure, Profitability, and the Implementation of Good Corporate Governance on Earnings Quality and then examine the impact on Company Value amid the Covid-19 pandemic. The following research will include comparative studies on companies in Indonesia and Malaysia. This research uses quantitative methods with a causality approach. Purposive sampling is a research methodology used in sampling techniques. This research was conducted on companies listed on the Indonesia Stock Exchange and the Malaysia Stock Exchange during the period 2019 to 2021. The findings of this research reveal that there are differences between Indonesia and Malaysia. The findings of a study conducted in Indonesia show that factors such as capital structure, profitability and corporate governance have a significant influence on earnings quality. However, the findings of a study conducted in Malaysia show that only profitability has an influence on earnings quality. The findings of this research also indicate that companies located in Indonesia and Malaysia in terms of the influence of capital structure and corporate governance on earnings quality have no impact on company valuation. The influence of profitability on earnings quality in Malaysia has an impact on company value.